A novel negative stiffness magnetic spring design for vehicle seat suspension system. (June 2020) - Tu, Lixin; Ning, Donghong; Sun, Shuaishuai; Li, Wenxing; Huang, Hua; Dong, Mingming; Du, Haiping
Highlights: A novel passive negative stiffness spring design for the seat suspension. A nonlinear seat suspension dynamic model and control. 28.8% vibration reduction can be achieved compared with the passive system. Abstract: By employing a couple of columnar magnets with a specific arrangement, a negative stiffness magnetic spring (NSMS) is designed, modelled and then experimentally validated in this paper. Such a magnetic spring with negative stiffness can be used for a semi-active seat suspension to achieve vibration reduction on vehicle drivers. Extensive simulation analysis and experimental validation based on static and vibration responses reveal that NSMS brings the beneficial low dynamics stiffness for seat suspension and reduces the resonance frequency vibration during the vertical excitation without compromising loading capacity. Besides, a semi-active seat suspension system with the NSMS can achieve excellent performance of low-frequency vibration suppression (around 28.8 % acceleration reduction under random excitation).